Low-temperature-fabricated ZnO, AZO, and SnO2 nanoparticle-based dye-sensitized solar cells - Kim, Hong Hee; Park, Cheolmin; Choi, WonKook; Cho, Sungjae; Moon, ByungJoon; Son, Dong Ick (KOREAN PHYSICAL SOC, 2014)
The authors investigated the microstructural and the electrical properties of ZnO, AZO, and SnO2 based dye-sensitized solar cells (DSSCs) fabricated using a low-temperature-processed (200 A degrees C) dye-sensitized ZnO, AZO, and SnO2 nanoparticle thin film and a Pt catalyst deposited on ITO/glass by RF magnetron sputtering. A hydropolymer containing PEG (poly ethylene glycol) and PEO (poly ethylene oxide) is used to make uniformly-distributed ZnO, AZO, and SnO2 nanoparticle layer which forms a nano porous ZnO, AZO, and SnO2 network after heat treatment. The layer is then dye sensitized and sandwiched between two electrodes in an electrolyte to make a DSSC device. The highest measured parameters, the short-circuit current density (J (sc) ), the open circuit potential (V (oc) ), the fill factor (FF), and power conversion efficiency (eta), of the DSSC fabricated wander optimized conditions were observed to be 5.10 mA/cm(2), 0.61 V, 0.46, and 1.43%, respectively.
Keywords: FILMS